Improving teachers’ understanding of reproductive health and sexuality education in special schools - Tati Hernawati; Imas Diana Aprilia; Agus Irawan Sensus; Euis Heryati; Prinanda Gustarin Ridwan; Zulfa Rahmah Effendi; Arif Prawira; Wina Tri Saptari; Tarishah Aulia; Fitri Mulyani (Inovasi Kurikulum)
The inability to achieve complete independence in students with special needs has the potential to make this group vulnerable to problems, including reproductive health and sexuality problems. These problems are suspected to be due to the lack of understanding and perception of teachers in the concept and implementation of reproductive health and sexuality education in Special Schools (SLB). This study was conducted to see teachers' understanding of reproductive health and sexuality education for students with special needs. Using a quantitative approach with a one-group pretest-posttest design, this study involved 15 teachers from six SLBs in Bandung City who were selected using the purposive sampling method. The data obtained were analyzed using the Wilcoxon Signed-Rank Test. The results of the study showed a significant increase in the average score, indicating that the efforts made could improve teachers' understanding of reproductive health and sexuality education. Teachers felt more prepared to deal with the problems of students with special needs regarding reproductive health and sexuality after participating in competency refresher courses by participating in training or discussions. Training and discussions that are planned systematically, sustainably, and comprehensively can improve teacher competence and, more broadly, can improve the quality of reproductive health and sexuality education in SLB.